An endometrial receptivity scoring system basing on the endometrial thickness, volume, echo, peristalsis, and blood flow evaluated by ultrasonography - Zhang, Chun-hui; Chen, Cheng; Wang, Jia-rui; Wang, Yue; Wen, Si-xi; Cao, Yan-pei; Qian, Wei-ping (Frontiers in Endocrinology, 2022)
Background: Establishing a successful pregnancy depends on the endometrium and the embryo. It is estimated that suboptimal endometrial receptivity account for one-third of implantation failures. Despite the indepth understanding of the processes associated with embryo-endometrial cross-talk, little progress has been achieved for diagnosis and treatments for suboptimal endometrial receptivity. Methods: This retrospective study included women undergoing their first frozen-thawed embryo transfer (FET) cycles at our reproductive medicine center from March 2021 to August 2021. Transvaginal three-dimensional (3D) ultrasound was performed in the morning on the day of embryo transfer for all the thawed embryo transfer patients, to evaluate endometrial receptivity, including endometrial thickness, echogenicity, volume, movement and blood flow. Results: A total number of 562 patients of FET with 315 pregnancies (56.0%) was analyzed. It was found that only the echo of the endometrial central line was different between the pregnant group and non-pregnant group. Other parameters, such as endometrial thickness, volume, endometrial peristalsis, or the endometrial blood flow were not statistically different between the two groups. Then, according to the relationship between the different groups and the clinical pregnancy rate, a score of 0 to 2 was respectively scored. The sum of the scores for the six items was the patient's endometrial receptivity score. It showed that the clinical pregnancy rate increased as the endometrial receptivity score increased, and when the receptivity score reaches at least 5, the clinical pregnancy rate is significantly improved (63.7% versus 49.5%, P=0.001). Conclusion: We developed an endometrial receptivity scoring system and demonstrated its validity. It may aid clinicians in choosing the useful marker in clinical practice and for informing further research.